Soil vertical distribution and migration characteristics and vegetation adaptive restoration in areas disturbed by power transmission and transformation projects - Kai Che; Jinxing Yu; Yukun Ju; Xuan Zhao; Yunqian Gong; Chongming Chen (Discover Applied Sciences)
Abstract With the continuous expansion of the construction scale of power transmission and transformation projects, their impact on surrounding soil and vegetation is increasingly receiving attention. The purpose of this study is to explore in depth the vertical distribution and migration characteristics of soil in disturbed areas of power transmission and transformation projects, as well as the adaptive restoration mechanism of vegetation. This is of great significance for evaluating the ecological impact of power transmission and transformation projects and formulating reasonable ecological restoration strategies. Select a large-scale power transmission and transformation project as the research object, and arrange sampling points in four different directions in the disturbance zone and the undisturbed zone to obtain sample information of the research area. Select indicators such as diversity index and Simpson dominance index to accurately quantify the status of vegetation adaptive restoration. Measure the content of elements such as As, Sb, Pb, Zn, organic matter, and total nitrogen in soil to accurately analyze the vertical distribution and migration characteristics of soil. The results indicate that the vertical migration ability of soil profiles follows the pattern of Zn > Pb > As > Sb. Compared with natural reserves, the species diversity in the disturbed areas of power transmission and transformation projects is significantly reduced. From the perspective of soil, the organic matter content in the disturbed area of power transmission and transformation projects is lower than that in the undisturbed area, which has a negative impact on vegetation growth. Based on the above results, artificial intervention can be used to promote vegetation restoration by applying organic fertilizers, straw, and sowing grass seeds in the disturbed areas of power transmission and transformation projects.